2017
DOI: 10.5858/arpa.2016-0530-ra
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applications of Immunohistochemistry in the Diagnosis of Genitourinary Tumors

Abstract: Context.-Pathologic diagnosis of tumors in the genitourinary system can be challenging based on morphology alone, particularly when diagnostic material is limited, such as in core biopsies. Immunohistochemical stain can be a useful tool to aid in the diagnosis.Objective.-To provide an update on practical applications and interpretation of immunohistochemical stains in the diagnosis of tumors in prostate, kidney, bladder, and testis. We particularly focus on difficult differential diagnoses, providing our insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…CK7 expression was observed in both healthy and neoplastic cells and CK7 staining has prognostic value in an IHC-based analysis of renal cell neoplasms (34, 35). In addition, both chromophobe RCC and clear cell papillary RCC are typically positive for CK7, while conventional ccRCC is usually not, which grants it pivotal importance in the differential diagnosis among clear cell renal neoplasms (36). In 2018, Gonzalez et al suggested that CK7 immunoreactivity in ccRCC is variable and the extent of staining depends on the clinical-histopathological parameters including grade and architectural growth patterns of the tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…CK7 expression was observed in both healthy and neoplastic cells and CK7 staining has prognostic value in an IHC-based analysis of renal cell neoplasms (34, 35). In addition, both chromophobe RCC and clear cell papillary RCC are typically positive for CK7, while conventional ccRCC is usually not, which grants it pivotal importance in the differential diagnosis among clear cell renal neoplasms (36). In 2018, Gonzalez et al suggested that CK7 immunoreactivity in ccRCC is variable and the extent of staining depends on the clinical-histopathological parameters including grade and architectural growth patterns of the tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…These RCC subtypes include clear-cell tumors, such as clear-cell carcinoma (ccRCC), chromophobe RCC (ChRCC), clear-cell papillary RCC (CCPRCC), and microphthalmos translocation family RCC (MiT RCC). Alternatively, eosinophilic tumors can be seen in papillary RCC (PRCC), CCRCC, ChRCC, eosinophilic variants, renal oncocytoma (RO), and acquired cystic disease RCC (ACD-RCC) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The 4 most common types of RCC are clear cell RCC, papillary RCC, chromophobe RCC, and recently recognized clear cell papillary RCC. Immunohistochemical workup of renal cell neoplasms has been thoroughly reviewed previously 31 ; however, new entities have emerged in recent years. 32,33 These new tumors are rare and can be difficult to diagnose without special immunohistochemical and/or molecular studies.…”
Section: Kidneymentioning
confidence: 99%